Potentially preventable hospital separations related to oral health: a 10‐year analysis. (19th May 2015) - Kruger, E; Tennant, M
Abstract: Background: The aims of this study were to assess the rates of hospitalizations for potentially preventable dental conditions over a 10‐year period in Western Australia; to analyse trends over 10 years in rate changes of hopitalizations; and to analyse the mix of preventable dental conditions by age group and Aboriginal status. Methods: The principal diagnosis, as classified by the International Classification of Disease (ICD‐10AM), was used to select hospitalization data for all patients who were discharged from hospital in Western Australia for the financial years 1999–2000 to 2008–2009, for a potentially preventable oral health condition. Results: Over a 10‐year period more than 65 000 people were hospitalized. Population rates of hospitalization increased significantly over the period for both Aboriginal and non‐Aboriginal population groups. Admission rates were higher for Aboriginal people. Children under 14 were more likely to be admitted; the most common condition that required hospitalization was dental caries, and the highest rates of hospitalization were for those from the most socio‐economically disadvantaged areas. Conclusions: These hospitalizations remain a considerable and increasing financial burden on health budgets. An increase in efforts is necessary to curb escalating government health expenditure by reducing avoidable and preventable oral health related hospitalizations.